2022
DOI: 10.1021/acs.jpcb.2c01517
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Dynamics of Positively and Negatively Charged Aromatics and Their Isoelectronic Neutral Analogs in Aqueous Solutions

Abstract: In this study, we investigated the temperature dependence of intermolecular vibrations and orientational dynamics in the aqueous solutions of imidazole hydrochloride, imidazole, sodium triazolide, and triazole using femtosecond Raman-induced Kerr effect spectroscopy (fs-RIKES) and steady-state Raman spectroscopy. The difference low-frequency Raman spectra under 250 cm–1 of the aqueous solutions relative to the neat water showed that the spectral shoulder in the high-frequency region at 60–100 cm–1, assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…In addition, the peak shifted to the low-frequency side with increasing temperature. This type of temperature-dependent spectral feature was commonly observed in nonaromatic cation-based ILs, including phosphonium-based ILs. , Notably, each liquid/solution including IL shows a unique line shape in the difference spectrum between the low-frequency spectra at 293 K and a higher temperature, and the line shape of the difference spectrum is different from that of the Bose–Einstein thermal occupation factor. ,, …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, the peak shifted to the low-frequency side with increasing temperature. This type of temperature-dependent spectral feature was commonly observed in nonaromatic cation-based ILs, including phosphonium-based ILs. , Notably, each liquid/solution including IL shows a unique line shape in the difference spectrum between the low-frequency spectra at 293 K and a higher temperature, and the line shape of the difference spectrum is different from that of the Bose–Einstein thermal occupation factor. ,, …”
Section: Resultsmentioning
confidence: 81%
“…Figure 6 shows that the line shapes of the three ILs were rectangular triangles with a peak at ∼20 cm shows a unique line shape in the difference spectrum between the low-frequency spectra at 293 K and a higher temperature, and the line shape of the difference spectrum is different from that of the Bose−Einstein thermal occupation factor. 99,100,105 The peak frequencies, ν p , of the spectra for the three ILs are plotted as a function of temperature to illustrate the temperature dependence of the low-frequency spectrum semiquantitatively (Figure 8). The details of the analysis procedure used in this study have been previously reported elsewhere.…”
Section: Liquid Properties: Glassmentioning
confidence: 99%